Knowledge of the professional functions of the veterinarian among residents of Lima - Peru: an exploratory study - Riques, Danae (2022)
The aim of this study was to determine the knowledge of the population of Lima about the professional functions of the veterinarian (VM) A study was developed based on virtual surveys aimed at residents of Metropolitan Lima, in which recognized functions of veterinary doctors were shown. The respondents had to give their opinion if the functions corresponded exclusively to the VM, shared with other professions or if they were attributed to other professions. In total, 671 valid surveys were obtained. The main functions attributed exclusively to the VM were to treat or prevent diseases in pets (87.6%), to promote responsible pet ownership (76.8%), to control dogs or other stray animals (67.5%), to investigate the form of transmission of animal diseases (62.4%). Likewise, the functions attributed to the VM and other professionals were: rescuing animals in disaster situations (60.7%), educating the population in the prevention of trafficking wild animals and their use as pets or ornaments (55.9%), participating in scientific research and manufacturing of biological products for the animal industry (53.9%), training the population in prevention of animal diseases in disaster situations (52.8%), taking care of the production and reproduction of animals for human consumption (51.0%) and sanitary control of trade in products and by-products of animal origin from Peru to other countries and vice versa (50.2%). On the other hand, the main function not attributed to VM was participating in actions related to climate change or global warming (53.1%). It was concluded that it is important to disseminate the functions of the VM so that the authorities and society recognize them and thus prevent their area of work development from being restricted.